Terrestrial locomotion in elongate fishes: exploring the roles of morphology and substrate in facilitating locomotion. (27th May 2020) - Mehta, R. S.; Akesson, K.; Redmann, E.; McCarty‐Glenn, M.; Ortega, R.; Syed, S.; Yap‐Chiongco, M.; Jacquemetton, C.; Ward, A. B.
Abstract: Highly elongate body plans have evolved multiple times in the Actinopterygii, and members of many of these groups are known to use lateral undulation on land. Here, we quantified components of the axial skeleton for four phylogenetically disparate actinopterygian fishes and one sarcopterygian to determine whether axial morphology may affect their locomotor kinematics. We tested species in water and on two terrestrial substrates: loose wet pebbles and wet sand. Differences in axial morphology translated to differences in wavelengths, amplitudes, and frequencies at the center of the body and tail while swimming, but overall, we consistently observed a similar shift in kinematic patterns when fish were moving on the two terrestrial treatments. Generally, our kinematic data support our hypothesis that elongate fishes increased their wave frequency and shorten their wavelengths on terrestrial substrates but we also observed lower wave amplitudes contrary to our prediction. As anticipated, animals exhibited a higher distance ratio (DR), our metric of locomotor efficiency, at the head, center of the body, and tail in aquatic trials. DRs were between 25% and 50% higher in water compared to terrestrial treatments. Locomotion was less effective on wet sand substrate compared to loose wet pebble substrate as exhibited by the discrepancy in DRs and wave patterns along the fish. These data suggest that loose wet pebble substrates do indeed provide vertical points for lateral force transmission and that highly elongate fish have an advantage when moving along this substrate. Our species varied greatly in their total vertebral numbers, 93–129, and in their proportion of precaudal (42–102) and caudal vertebral numbers (10–64). Therefore, despite major differences in vertebral proportions, we find that fishes with anguilliform body plans share similar suites of kinematic patterns within aquatic versus terrestrial treatments and that a pebble substrate can better facilitate axial movements. Abstract : Swimming and terrestrial locomotion were quantified for four fish species with an anguilliform body plan. We tested the species in water and on two terrestrial substrates: loose wet pebbles and wet sand. Although swimming kinematics differed between species, terrestrial movements exhibited more similarities, and in all cases, pebble substrate facilitated more direct and efficient movements. The disparity in kinematics between species when tested in water and on land is particularly interesting as these highly elongate fishes differed greatly in their vertebral proportions.